US defense politics the origins of security policy - Sapolsky, Harvey M.; Gholz, Eugene 1971-; almadge, Caitlin (Routledge, 2014)
This textbook provides an accessible overview of US defense politics for upper-level students. This new edition has been fully updated and revised, with a new chapter on intelligence and new material on unmanned drones, women in the military, the Tea Party, and other key issues. Analyzing the ways in which the United States prepares for war, the authors demonstrate how political and organizational interests determine US defense policy and warn against over-emphasis on planning, centralization, and technocracy. Emphasizing the process of defense policy-making rather than just the outcomes of that process, US Defense Politics departs from the traditional style of many existing textbooks.